Dissolution and Mechanism of Tincal in Ammonium Carbonate Solutions - YILDIZ*, ADNAN; SALIH NAS†, M.; KUBILAY†, SENOL; YILMAZ†, SINAN (Asian Journal of Chemistry, 2009)
In this paper the dissolution and mechanism of tincal, sodiumtetraborate decahydrate (Na2B4O7·10H2O), in ammonium carbonatesolutions using the effects parameters of reaction temperature, solutionconcentration, solid to liquid ratio, particle size and stirring speed. Theresults showed that the dissolution rate increased with increasing solutionconcentration and reaction temperature and increased with decreasingparticle size and solid to liquid ratio. It was also determined that stirringspeed exerted no significant effect on dissolution rate.